Geometrical Effect On Hydraulic Characteristics Of Free Surface Breakwater: An Experimental Study - Mohd Rafii, Ahmad Amin Akmal (IRC, 2019)
The paper is a research on the design of breakwater which can performs well in reducing the wave transmission coefficient for unidirectional monochromatic wave condition. To solve the problem faced by PETRONAS to safeguard the northen part of Kerteh jetties during monsoon and to provide a safe zone for “change of guard” operation near with the port, the free surface breakwater is the best initiative to use.